The Roles of Neuropilin 2/VEGF-C Axis in a Series of Recurrent Lymphangioma - Yan, Xueqiang; Zheng, Nannan; Xiong, Xiaoli; Duan, Xufei; Yang, Jun; Bian, Hongqiang; Zhu, Zhenchuang; Xiong, Xiaofeng; Chen, Xuyong (European Journal of Pediatric Surgery, 2020)
Introduction Vascular endothelial growth factor (VEGF) and its receptor act as a major contributor to lymphangioma, but their role on nonrecurrent and recurrent lymphangiomas remain unclear. We aim to investigate those factors in the generation of recurrent lymphangioma.Materials and Methods Patients diagnosed with lymphangioma from January 2005 to December 2012 in our hospital were collected and divided into nonrecurrent and recurrent lymphangiomas. The clinical characteristics including age, sex, symptoms, location, and size of lymphangioma were collected. Surgical resection samples were collected for histology, protein and mRNA detection of VEGF-C, VEGF receptor-3 (VEGFR-3), and neuropilin 2 (Nrp2). Follow-ups including lymphangioma recurrent and the local symptoms such as ulcer were reviewed.Results A total of 80 patients aged from 5 months to 12 years were enrolled in this study, 51 patients had no recurrence and other 29 patients suffered from recurrent lymphangioma. There was no significant difference in demographic data and clinical characters between the two groups (p > 0.05). Immunohistochemistry staining showed that VEGFR-3 remained unchanged between nonrecurrent and recurrent lymphangiomas (p > 0.05), and VEGF-C and Nrp2 were significantly increased in recurrent lymphangioma compared with nonrecurrent lymphangioma (p < 0.05). The same expression trend was proved as detected by protein and mRNA levels.Conclusion The VEGF-C/Nrp2 axis was significantly increased in the recurrent lymphangioma, indicating that VEGF-C/Nrp2 targeted therapy may serve as a potential therapeutic strategy for recurrent lymphangioma.
Keywords: recurrent lymphangioma; vascular endothelial growth factor; vascular endothelial growth factor receptor; neuropilin 2